ASSESSMENT OF NUTRITIONAL QUALITY OF 'SHIDAL' A FERMENTED FISH PRODUCT OF NORTHEAST INDIA - Majumdar, Ranendra Kumar; Basu, S.; Nayak, B. B. (Journal of Indian Fisheries Association, 2009)
'Shidal' is a salt-free fermented fish product prepared from Puntius ss.caught in late monsoon period. Shidal is very popular amongst the inhabitants of Northeast India. The fermentation process of this product takes four to six months in anaerobic condition till the product gains a characteristic flavour and colour. Detailed studies on the biochemical and nutritive qualities of this product are very few. Therefore, in this paper we report the results of theproximate analysis, amino acid and fatty acid compositions. The results suggest that 'Shidal' is a rich source of amino acids as well as of essential fatty acids like linoleic and linolenic acids. The n-3/n-6 ratio was found 0.51.Keywords: Shidal, fermented fish, Puntius sp., PUFAs.